Analysis of Battery Management System Using Lithium Ferro Phosphate for E-Vehicle (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Common rechargeable batteries with unique properties and uses are lead-acid and lithium ferrophosphate (LiFePO4) batteries.  In terms of important factors including energy density, cycle life, charging efficiency, cost, and environmental impact, several battery technologies are succinctly compared in this abstract.  LiFePO4 batteries have a higher energy density than lead-acid batteries, which are renowned for their longevity and dependability.  They are frequently utilized in backup power systems and automotive starting, lighting, and ignition (SLI) applications, and they are appropriate for applications needing large discharge currents.  However, compared to LiFePO4 batteries, lead-acid batteries have a shorter cycle life, less charging efficiency, and greater maintenance needs.  However, compared to lead-acid batteries, LiFePO4 batteries have a higher energy density, a longer cycle life, and improved charging efficiency.  They are perfect for electric cars, renewable energy storage systems, and portable electronics since they are lighter and have a slower rate of self-discharge.  Because of their enhanced performance and longer longevity, LiFePO4 batteries frequently offer better long-term value despite their higher initial cost.  Because lead-acid batteries include hazardous substances like lead and sulfuric acid, which can pollute the environment if improperly disposed of or recycled, they provide a significant environmental risk.  However, because LiFePO4 batteries don't contain heavy metals and are less likely to have thermal runaway or fire, they are thought to be more environmentally friendly.  In summary, LiFePO4 batteries are the favored option for many contemporary energy storage requirements due to their greater performance, longer lifespan, and reduced environmental effect, even though lead-acid batteries have advantages in some applications.  But in the end, choosing between these two battery technologies comes down to particular needs like price, weight, energy density, and environmental factors.